A review on the recent advancements in graphene-based membranes and their applications as stimuli-responsive separation materials. Issue 38 (20th September 2021) - Austria, Hannah Faye M.; T. M., Subrahmanya; Setiawan, Owen; Widakdo, Januar; Chiao, Yu-Hsuan; Hung, Wei-Song; Wang, Chih-Feng; Hu, Chien-Chieh; Lee, Kueir-Rarn; Lai, Juin-Yih
Abstract : Graphene and its derivatives that are key players in the field of membrane technology, have amassed a huge amount of publications in the past years regarding their fabrication, properties, applications, and most recently, their utilization as smart membranes. Abstract : Graphene possesses a set of unique physicochemical properties including exceptional mechanical, thermal, and electrical properties, making it an excellent candidate for constructing materials for a wide range of applications including the vast field of separation technology using membranes. Separation membranes based on graphene and its derivatives have shown satisfactory results over the years when applied to environmental systems such as wastewater treatment and gas purification, which is a great contribution in sustainable development. However, membrane separation research is generally performed using conventional membranes with fixed driving force and separation properties that suffer from fouling and decline in performance upon long-term use or when a change in the environmental conditions occur. These issues can be solved by employing an emerging technology that makes use of graphene and its derivatives combined with polymeric materials to construct stimuli-responsive or "smart" membranes that respond to the changes in their environment such as chemical cues, temperature, pressure, and external fields, and have a self-regulated separation performance due to reversible physicochemical properties. In this review, we present a report on the recent advancements on graphene-based separation technology including a concise discussion on the basic structure and properties of graphene and its derivatives, various membrane fabrication methods, and their employment on the different areas of membrane separation. More importantly, the main focus of this paper is to evaluate the design and utilization of graphene-based smart separation membranes.